IN VITRO Î±-AMYLASE AND Î±-GLUCOSIDASE INHIBITOR ACTIVITY OF ABUTILON INDICUM LEAVES - Pant, Geetika; Sai, Krishna; Babasaheb, S; Reddy, Rajashekar; G, Sibi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Postprandial hyperglycemia caused by the hydrolysis of carbohydrates by pancreatic Î±-amylase and intestinal Î±-glucosidase is a serious condition and inhibition of these enzymes is an effective way in the management of diabetes mellitus. Abutilon indicum (L.) Sweet leaves were used to determine their in vitro Î±-amylase and Î±-glucosidase inhibitory activity. Various concentrations from 10 Âµg ml-1 to 160 Âµg ml -1 were prepared in methanol along with the standard antidiabetic drug, acarbose. There was a dose dependent percent inhibition by the extract against Î±-amylase (7.12% - 41.31%) and Î±-glucosidase (8.01% - 36.13%). Logarithmic regression analysis revealed the IC50 of 129.89 Âµg ml-1 (Î±-amylase) and 137.61 Âµg ml-1 (Î±-glucosidase) with a potency and preference for Î±-amylase over Î±-glucosidase inhibition by the A. indicum leaf extract.Â